2018
DOI: 10.1002/jhet.3438
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Mediated Synthesis, Biological Evaluation, and Molecular Docking Study of 4‐(1H‐pyrazol‐4‐yl)‐polyhydroquinolines as Potent Antitubercular Agents

Abstract: A series of 4‐(1H‐pyrazol‐4‐yl)‐polyhydroquinolines were synthesized through one‐pot four‐component Hantzsch condensation of 1,3‐diphenyl‐1H‐pyrazole‐4‐carbaldehydes, ammonium acetate, dimedone, and alkyl acetoacetate in glycerol as a green reaction medium. The structures of the compounds are verified by spectroscopic methods and screened for their antimicrobial activity against Mycobacterium tuberculosis H37RV strain. Almost all the synthesized derivatives reveal excellent antitubercular activity based on min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 66 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…With a minimal inhibitory concentration of 1.6 μg/mL, the compounds (210h) and (210k), showed significant antitubercular efficacy. (Scheme 43) [58] Viswanadh Nalla et al created a series of 20 novel chromone embedded [1,2,3]-triazoles derivatives using a simple and convenient synthesis technique starting with 2-hydroxy acetophenone. To synthesize the target derivative, Copper sulphate pentahydrate, sodium ascorbate, and distilled water were added progressively to a stirred solution of azide and aliphatic/aromatic alkynes in t-butanol.…”
Section: Ms Komal Saini Has Been Working As Anmentioning
confidence: 99%
See 1 more Smart Citation
“…With a minimal inhibitory concentration of 1.6 μg/mL, the compounds (210h) and (210k), showed significant antitubercular efficacy. (Scheme 43) [58] Viswanadh Nalla et al created a series of 20 novel chromone embedded [1,2,3]-triazoles derivatives using a simple and convenient synthesis technique starting with 2-hydroxy acetophenone. To synthesize the target derivative, Copper sulphate pentahydrate, sodium ascorbate, and distilled water were added progressively to a stirred solution of azide and aliphatic/aromatic alkynes in t-butanol.…”
Section: Ms Komal Saini Has Been Working As Anmentioning
confidence: 99%
“…With a minimal inhibitory concentration of 1.6 μg/mL, the compounds (210h) and (210k), showed significant antitubercular efficacy. (Scheme 43) [58] …”
Section: Chemistry Of Different Heterocycle Scaffolds As Antitubercul...mentioning
confidence: 99%
“…Jamale et al reported the preparation of 4-(1Hpyrazol-4-yl)-polyhydroquinoline derivatives 114 by one-pot four component Hantzsch condensation reaction (Scheme 32). [72] The reaction involved 1,3-diphenyl-1H-pyrazole-4-carbaldehydes 111, alkyl acetoacetate 112, ammonium acetate 113, dimedone 106 and promoted by glycerol in an efficient manner by conventional heating at 95 °C for 2 h.…”
Section: Synthesis Using Metal Free Approachmentioning
confidence: 99%
“…Jamale et al (17) showed that their polyhydroquinoline derivatives had significant potential as an antimicrobial. Some of the compounds were effective against Mycobacterium tuberculosis, which is an extremely difficult microorganism to eradicate.…”
Section: Antimicrobial Activitymentioning
confidence: 99%